RELACION ENTRE LA DOCENCIA Y LA FORMACION DE VALORES EN EL DECIMO CURSO DEL CICLO BASICO DEL INSTITUTO TECNOLOGICO SUPERIOR ''GUAYAQUIL'', PERIODO 2007-2008. - CARMELINA ELIZABETH VILLEGAS DE CARRION (2008)
RELATIONSHIP BETWEEN TEACHING AND THE FORMATION OF VALUES IN THE TENTH YEAR OF THE BASIC CYCLE OF THE INSTITUTE OF SUPERIOR TECHNOLOGY ''GUAYAQUIL'', PERIOD 2007-2008.